Real-world pharmacological treatment of patients with postpartum depression in China from 2016 to 2020: A cross-sectional analysis - Kai Sun; Xianli Wang (Elsevier, 2022)
Objective: To determine the use and tendency of drugs for postpartum depression (PPD) in nine cities across China in 2016-2020 in order to provide a reference for drug use in the clinic. Methods: The prescription data of drugs for PPD outpatients in nine cities (Beijing, Chengdu, Guangzhou, Harbin, Hangzhou, Shanghai, Shenyang, Tianjin and Zhengzhou) across China in 2016-2020 were extracted from the Hospital Prescription Analysis Cooperation Project database of the Hospital Pharmacy Professional Committee of Chinese Pharmaceutical Association. A cross-sectional analysis was then conducted of patient age, total prescription quantity, average prescription amount, defined daily doses (DDDs) of drugs, defined daily cost (DDC) of drugs and so on. Results: In 2016-2020, more than half of PPD patients in these nine cities were distributed in first-tier cities (Beijing, Shanghai and Guangzhou), and were mainly aged 30-39 years. During the five-year period, the prescription quantity, total prescription amount and average prescription amount increased by 20.95%, 35.41% and 11.02%, respectively. In terms of prescription frequency and prescription amount, selective serotonin reuptake inhibitors (SSRIs) ranked first, followed by serotonin-norepinephrine reuptake inhibitors (SNRIs). With regard to DDDs, escitalopram, sertraline, paroxetine and venlafaxine ranked high, and sertraline was top year by year. The DDC of vortioxetine and milnacipran was greatest, while that of escitalopram, olanzapine and quetiapine declined sharply after being included in the China centralized drug-procurement program. Conclusion: The number of PPD patients and the total prescription amount in the nine cities across China increased in 2016-2020. SSRIs and SNRIs were the main drugs for PPD treatment. Due to the national centralized drug-procurement policy, there has been a great reduction in the DDC, lightening the economic burden on patients.